Dynamic capabilities and business model innovation in sustainable family farming - Olívia Prado Schiavon; Márcia Ramos May; Andréa Torres Barros Batinga de Mendonça (Innovation & Management Review, 2022)
Purpose - The study aims to understand how dynamic capabilities (DCs) contribute to business model innovation (BMI) in sustainable family farming. The agrifood sector has been seeking solutions for the development of agroecological markets. Thus, the authors have analyzed the challenges imposed to innovation and sustainability strategic management and the value proposition to sustain the business over the years. Design/methodology/approach - Considering the complexity of organizations and through an exploratory multiple case study of initiatives identified in the Organic Fair of Curitiba's Passeio Público, it was possible to analyze the evolution of the business models (BMs) and the fair itself. Furthermore, it was possible to identify the DCs within the influence of agroecosystem elements on the innovation development. Findings - Analyzing each case individually, the authors understood the different dimensions of the evolution of BMs considering the organizational complexity. The authors conclude that the balance between organizational practices and changes in the environment, engagement and learning plays a significant role in the developing competitive advantage. The same applies to the patterns that precede the development of DCs and BMs. Originality/value - The article investigates innovation in agroecological BMs from a dynamic capability perspective. The agroecological BM is a subject that is still little discussed in the literature. In addition, the authors chose a context that includes socioenvironmental aspects and a few specificities of family farming in Brazil.
Keywords: 650; Dynamic capabilities; Business model innovation; Agroecology; Sustainable development